Pengaruh Kompetensi Guru Dan Lingkungan Pesantren Dalam Pembelajaran Kitab Adabul ‘Alim Wal Muta’alim Terhadap Karakter Santri Di Pondok Pesantren Tebuireng Jombang - Nurjamilatul Muhairirah; Rifan Zaini; Diska Firzan N; Fadhil Ismail; Imro’atul Ma’rifah (Journal on Education, 2025)
This study aims to analyze the influence of teacher competence and pesantren environment on the character of santri at Pondok Pesantren Tebuireng Jombang. A quantitative approach with ordinal logistic regression analysis (OLR) was used to examine the relationship between the independent variables (teacher competence and pesantren environment) and the dependent variable (santri character). The sample consisted of 50 students from MTs Salafiyah Syafiiyah, selected using cluster sampling. Data were collected using a Likert scale questionnaire (1-4). The results of the study show that teacher competence has a significant positive influence on the development of santri character, with a significance value of 0.000, which is smaller than the alpha level of 0.05. This indicates that the higher the teacher's competence, the better the character of the santri. In contrast, the pesantren environment was found to have no significant effect on santri character, with a significance value of 0.059, which is greater than 0.05, meaning the second hypothesis is rejected. The ordinal logistic regression analysis (OLR) also indicates that teacher competence plays a more dominant role in shaping santri character